Study, Analysis and Development of Bani Na’im Medium Voltage Electric Network - Aburaiya, Bahaa; ALkhdour, Qassam (My University, 2017)
The project is to present offer proposal complete study of the medium voltage electrical network in Bani Na’im town near Hebron. The study methodology is to collecting data and information needed to discover the network problems using E-TAP program, and discuss the result of load flow. That is made the essential developments and improvements on the network such as reducing the losses, improving the power factor, achieving the network stability and increasing its efficiency. In the other hand, the project finds solutions for the problems that exist such as, low power factor, losses in electrical network, and voltage drop. Work necessary adjustments and developing to the network with considering the economic study needed to solving problems, and identify network development requirements with respect to source side and load side. .
Study, Analysis and Development of Bani Na’im Medium Voltage
CD ,30138 ,Number of pages 172 , in the store , طاقة 2/2017
Keywords: Electrical Engineering ,Electric Network